2014
DOI: 10.1118/1.4889469
|View full text |Cite
|
Sign up to set email alerts
|

WE-F-16A-02: Design, Fabrication, and Validation of a 3D-Printed Proton Filter for Range Spreading

Abstract: Purpose: To design, fabricate and test a 3D‐printed filter for proton range spreading in scanned proton beams. The narrow Bragg peak in lower‐energy synchrotron‐based scanned proton beams can result in longer treatment times for shallow targets due to energy switching time and plan quality degradation due to minimum monitor unit limitations. A filter with variable thicknesses patterned on the same scale as the beam's lateral spot size will widen the Bragg peak. Methods: The filter consists of pyramids dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The required number of energy layers can be significantly reduced using an energy smearing device such as a mini‐ridge filter (MRF). The usage of an MRF for range spreading in our Hitachi nozzle has been explored by Remmes et al . and Courneyea et al .…”
Section: Discussionmentioning
confidence: 99%
“…The required number of energy layers can be significantly reduced using an energy smearing device such as a mini‐ridge filter (MRF). The usage of an MRF for range spreading in our Hitachi nozzle has been explored by Remmes et al . and Courneyea et al .…”
Section: Discussionmentioning
confidence: 99%
“…The material used in this study was ultraviolet curable acrylic plastic. Other proton radiotherapy applications include 3D printed range spreading filter (22) and patient‐specific bolus for proton (23) . Our study focused on the fabrication process and characterizations of 3D‐printed patient electron bolus and proton compensator using FDM and SLS technologies with PLA and polyamide materials, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Users could modify the volume of the VGM (whether proportionally or not) by only changing the size of voxels in the FLUKA user routine file, and simultaneously precheck the 2D as well as 3D viewgraphs of the VGM in Flair. With the development of 3D printing, more and more radiation therapy centers use this technology to materialize the beam-modulated equipment 21,22 or human tissue. 23,24 In our current study, various factors potentially influenced the observed discrepancies across the design→ simulation validation→ 3D printing process for the models.…”
Section: Discussionmentioning
confidence: 99%